Economic status and family structure among the urban Chinese / Lim Su Yin - Lim , Su Yin (1983)
This report is a study of the family structure and kinship ties among the urban Chinese in Kuala Lumpur with special reference to the Chinese in traditional China. This report contains four chapters with the first chapter being the introduction, the second chapter is the literature review, the third chapter is the findings of the field research and the last chapter is the conclusion. Chapter One explains the aim of the study, concepts used, the methodology and a general outline of the urban Chinese in Kuala Lumpur. Chapter Two focus on the traditional Chinese society in China where a comparison was made between the peasants and the gentries. Chapter Three is on the findings of the field research and a comparison was made between the family structure and kinship ties of the Chinese in Kuala Lumpur and in traditional China. Chapter Four is the conclusion and it focus mainly on the changes that has taken place in the family structure and kin relationship and the factors which brought about these changes.